2019
DOI: 10.1002/ppul.24235
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐4 ‐590C/T gene polymorphism in Egyptian children with acute lower respiratory infection: A multicenter study

Abstract: Background Acute lower respiratory infection (ALRI) is the leading cause of child mortality, especially in the developing world. Polymorphisms in the interleukin 4 (IL‐4) gene have been linked to a variety of human diseases. Objectives To investigate whether the IL‐4 ‐590C/T (rs2243250) polymorphism could be a genetic marker for susceptibility to ALRIs in young Egyptian children. Methods This was a multicenter study conducted on 480 children diagnosed with pneumonia or bronchiolitis, and 480 well‐matched healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Thus, the T allele frequency and the homozygous T/T genotype prevailed in children with acute respiratory tract infections (pneumonia, brochiolitis) living in Egypt (OR = 1.3; 95 % CI = 1.07-1.56, P < 0.01 and OR = 2.0; 95% CI = 1.38-2.96, respectively) [32]. In patients with whooping cough, the homozygous T/T genotype (C589T) of the IL-4 gene frequency was higher than in healthy ones, and more than half of patients suffering from pyelonephritis (52.7 %) were carriers of the heterozygous C/T variant of this gene polymorphic region [33,34].…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the T allele frequency and the homozygous T/T genotype prevailed in children with acute respiratory tract infections (pneumonia, brochiolitis) living in Egypt (OR = 1.3; 95 % CI = 1.07-1.56, P < 0.01 and OR = 2.0; 95% CI = 1.38-2.96, respectively) [32]. In patients with whooping cough, the homozygous T/T genotype (C589T) of the IL-4 gene frequency was higher than in healthy ones, and more than half of patients suffering from pyelonephritis (52.7 %) were carriers of the heterozygous C/T variant of this gene polymorphic region [33,34].…”
Section: Discussionmentioning
confidence: 97%
“…As a result, levels of IL-4 itself exert an important influence on the balance of cytokines [ 11 ]. IL-4 acts as an anti-inflammatory and immunomodulatory factor, especially through its suppression effect over the secretion of proinflammatory cytokines IL-1, IL-6, IL-12, and TNF-alpha [ 12 ]. Studies have shown that levels of IL-4 and IL-4 mRNA are reduced in IBD patients, mainly Crohn’s disease patients, indicating a role for this cytokine in the pathophysiological process [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute lower respiratory infections (ALRI), primarily including pneumonia and bronchiolitis with typical clinical symptoms such as fever, cough, asthma, rale, and so forth, are among the most severe infectious diseases (Emam et al, 2019). ALRI leads to nearly one million deaths in children under five years of age every year, a much higher rate than all other childhood illnesses (UNICEF/WHO.…”
Section: Introductionmentioning
confidence: 99%